TEACHING PASSIVE VOICE THROUGH TRANSFORMATIONAL DRILL TECHNIQUE TO THE TENTH GRADE STUDENTS OF SMK MUHAMMADIYAH 1 PALU - Rahmah, Rahmah; Thamrin, Nur Sehang; Sahril, Sahril (Jurnal Kolaboratif Sains, 2020)
This research was conducted to find out that the use of transformational drill technique was effective to improve the students’ ability in learning passive voice. The research was pre-experimental research. The sample of the research was the tenth grade students of SMK Muhammadiyah 1 Palu that consisted of 29 students. The researcher employed total sampling technique. The researcher used two instruments, namely test and questionnaire. The data were analysed by statistical analysis. The result of data analysis show that the t-counted (13.9) was greater than the t-table (1.70). In short, transformational drill technique is effective to teach passive voice at the tenth grade students of SMK Muhammadiyah 1 Palu.Key words: Passive Voice, transformational drill technique.